ANALISIS PENGARUH INTERVENSI PEMERINTAH PUSAT TERHADAP RENCANA PEMBANGUNAN PEMERINTAH DAERAH KABUPATEN BANDUNG BARAT - Muhammad Dziki Zainal Arifin (PRAJA: Jurnal Ilmiah Pemerintahan, 2023)
West Bandung Regency is one of the regions in Indonesia which also has an independent and autonomous regional government system as the principle of decentralization is carried out and implemented at the regional government level. Law Number 23 of 2014 concerning Regional Government is the basic point of departure for the decentralization system in Indonesia and the distribution of rights and powers of regional governments in carrying out various programs in their regions as evidence of an autonomous and independent government. Decentralization also prioritizes regional capacity and authority to provide good public services to the community. Nonetheless, central government intervention into the local government system is something that cannot be avoided. Many steps and also central government programs have actually reduced local government from various aspects, especially aspects of regional planning. One of the things that can be seen in West Bandung Regency is that with the realization of a national strategic project, the regional government of West Bandung Regency has to re-adjust the plans they have made in the medium and long term.